Humoral responses against merozoite Plasmodium falciparum candidate vaccine antigens in pregnancy and infancy: influence of immunomodulatory factors - Gbaguidi, Mahugnon Léger Erasme (2024)
Background and Objectives: Plasmodium facilparum (Pf) malaria is one of most prevalent tropical infections in Benin, and pregnant women and children are at the highest risk. Although there is no effective vaccine, novel merozoite surface vaccine antigens have been proposed as potential targets for malaria control. Immune checkpoint molecules and the concomitant presence of soil transmitted helminths (STH) may interfere with the humoral response against malaria. This study was conducted to evaluate: i) the protective role of antibodies directed against candidate vaccine antigens obtained from the asexual stage of Pf, ii) the role of the immune check point HLA-G molecule on the humoral response against asexual stage of Pf, and iii) the influence of STH on the modulation of the anti-merozoite humoral responses, since malaria exhibits a Th1 and STH a Th2 response. Patients and Methods: Four-hundred Beninese women and their children were longitudinally followed-up along pregnancy, as well as their infants during the first two years of life, in the context of parasitological, immunological, socio-environmental, and epidemiological factors. Malaria and STH infections were actively recorded during follow-up of mothers (antenatal visits 1/2-ANV1/2, and at delivery-DEL) and infants (birth, and 6, 9, 12, 18 and 24 months of life). The antibody response (IgG1/2/3 and IgM) against Pf merozoite recombinant antigen vaccine candidates (AMA-125-545, MSP-119, MSP-2/3D7, MSP-2/FC27, MSP-3161-276, GLURP-R025-514 and GLURP-R2705-1178), and soluble HLA-G (sHLA-G) levels were quantified in plasma by ELISA. Results were adjusted by environmental factors and malaria treatment (intermittent preventive treatment in pregnancy: IPTp). Statistical analyses were performed using logistic linear, linear mixed regression, and cox-proportional regressions. Results: We observed that: i) with the exception of IgMs and specific antibody responses against MSP3, anti-merozoite IgG levels were lower at delivery after two doses of IPTp compared with no treatment. In particular, IgG2 decreased early in ANV2 (after the first dose of IPT) compared to ANV1; ii) during pregnancy, IgG antibodies against GLURP-R0, MSP2-3D7 and MSP1 conferred protection against peripheral and placental malaria infection, iii) previous pregnancy malaria infections and placental malaria decreased the transplacental antibody transfer, specifically for IgG1/3 against AMA1 and MSP1, which were the most frequently transferred to the fetus, iv) IgG antibodies did not protect children; however, IgM antibodies against MSP1, MSP2-3D7, MSP2-FC27, and MSP3 exhibited a more effective response against malaria in infants aged 18-24 months, v) sHLA-G levels were influenced by the labor period, the IPTp doses, and the +3003TT 3\'UTR genotype, vi) the overall increased levels of sHLA-G were correlated with decreased levels of IgG antibodies, particularly at term gestations, and vii) in infants, the STH infection after the age of one year modulated anti-merozoite IgM responses. Discussion: This is the first study to prospectively evaluate a large number of mothers, their infants, and 28 anti-merozoites responses, taking into account several confounding factors, to understand the dynamics of the humoral response against the Pf merozoite antigens. IgM responses should be taken into account in the design of childhood vaccines and IgG responses, particularly against MSP1, MSP2, and GLURP antigens, appear to be suitable and more promising candidates for malaria vaccines in pregnant women. sHLA-G levels during pregnancy were inversely correlated with most IgG antimerozoite antigens, while the presence of STH primarily modulated the IgM anti-merozoite responses in infants. Functional studies of the biological activity of anti-merozoite antibodies are necessary to reveal their protective role against Pf malaria in each clinical condition.